Event Marketing sebagai Bentuk Komunikasi Pemasaran Pemerintah Kabupaten Siak dalam Membentuk Brand Awareness "Siak the Truly Malay" - Lubis, Evawani Elysa; Rimayanti, Nita; Rumyeni, Rumyeni (Jurnal Politikom Indonesiana, 2019)
Marketing Event is one of marketing communication strategy that carried out by the district government to make their district become a tourist destination, and to get the investors who can invest their capital in theirs district. Beside, through marketing communication strategy the marketing event also performed regional brand and establish brand awareness in the minds of tourists. Therefore, the Government of Siak regency being aggressively promote their region by launching a regional brand that are “Siak The Truly Malay”, a slogan which reflected The Culture of Real Malay will be found in Siak. The purpose of this study want to analyze the determination of market segmentation is done by the Siak district government in implementing marketing communications strategies in build the brand awareness of the Siak The Truly Malay. The study also wants to understand that the marketing communication strategy in the form of marketing event which is undertaken by the Government of Siak in build the brand awareness and the media which used to promote the brand’s. The method which is used in the researches are qualitative, It’s is used five informants. The results of this study indicated that in unclear determination of market segmentation for tourists who are expected to visit Siak, meaning Siak District Government has not been able clearly identified their target market segments. While the strategy of marketing communication through marketing event which designed by Siak district government to build brand awareness 'Siak The Truly Malay' was not maximal because of the event is held not focus on culture only, but more to sporting events. The media which used to promote the event of 'Siak The Truly Malay' brand awareness are television, internet media, billboards, banners Keywords: Marketing Communication, Event Marketing, Brand Awareness